SISTEM INFORMASI PENJUALAN PAKAIAN DI TOKO LINDUNG BERBASIS WEB - Br Purba, Mawar Silvia; Nainggolan, Rena; Purba, Eviyanti Novita (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Toko Lindung is a shop that sells women's fashion and traditional karo fabrics, located at Jalan Pelita II No. 56 Pancur Batu. The sales system at this store is still done manually, namely coming directly to the store. The purpose of this research is to make it easier for customers to make fashion purchases without having to come directly to the store, so that in this research a website will be created to make it easier for customers to make purchases online. The sales website at Toko Lindung was built using an open source sublime programming tool based on HTML, PHP and MySQL database. With the existence of a web-based sales system, all transactions can be carried out more easily without being limited by distance and time. The results of this study are in the form of a web-based sales design, so with this web-based sales system, sales transactions and business processes will become easier.